Morule-like features in pulmonary adenocarcinoma associated with epidermal growth factor receptor mutations: two case reports with targeted next-generation sequencing analysis - Yoo Jin Lee; Harim Oh; Eojin Kim; Bokyung Ahn; Jeong Hyeon Lee; Youngseok Lee; Yang Seok Chae; Chul Hwan Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Morules, or morule-like features, can be identified in benign and malignant lesions in various organs. Morular features are unusual in pulmonary adenocarcinoma cases with only 26 cases reported to date. Here, we describe two cases of pulmonary adenocarcinoma with morule-like features in Korean women. One patient had a non-mucinous-type adenocarcinoma in situ and the other had an acinarpredominant adenocarcinoma with a micropapillary component. Both patients showed multiple intra-alveolar, nodular, whorled proliferative foci composed of atypical spindle cells with eosinophilic cytoplasm. Targeted next-generation sequencing was performed on DNA extracted from formalin-fixed paraffin-embedded samples of the tumors. Results showed unusual epidermal growth factor receptor (EGFR) mutations, which are associated with drug resistance to EGFR tyrosine kinase inhibitors, revealing the importance of identifying morule-like features in pulmonary adenocarcinoma and the need for additional study, since there are few reported cases.